Technology in Education: International Conference, ICTE 2014, Hong Kong, China, July 2-4, 2014. Revised Selected Papers - Li, K.C (Springer, 2015)
This book constitutes the refereed proceedings of the International Conference on Technology in Education, ICTE 2014, held in Hong Kong, in July 2014. The 18 revised full papers and 4 short papers presented were carefully reviewed and selected from 45 submissions. The papers are organized in topical sections on application of mobile technologies in e-learning; technology advancement in e-learning systems; innovations in e-learning pedagogy; open education and institution e-learning policy.